Survival and prognostic factors of patients with renal cell cancer with bone metastasis in the era of targeted therapy: A single-institution analysis - Du, YueJun; Pahernik, Sascha; Hadaschik, Boris; Teber, Dogu; Duensing, Stefan; Jäger, Dirk; Hohenfellner, Markus; Grüllich, Carsten (Urologic oncology, 2016)
To analyze the survival and prognostic factors of patients with renal cell carcinoma (RCC) with bone metastasis (BM). Data of all patients with RCC with BM treated between January 2006 and March 2015 were retrieved from our database and analyzed retrospectively. Overall survival (OS) from diagnosis of BM was analyzed for the whole cohort and selected subgroups. Statistical analyses of clinical and pathological variables were performed using Cox regression and the Kaplan-Meier method. A total of 114 patients were included. Median time from initial diagnosis of RCC to BM was 5.5 months (95% CI: 2.7-8.3). Median OS of the whole cohort was 9.6 months (95% CI: 5.5-13.6). On multivariate Cox regression analysis, targeted therapy (TT), resection of BM, and bisphosphonate treatment were favorable factors for the OS, whereas sarcomatoid features and high Fuhrman grade were unfavorable factors for OS. The median OS of 78 patients with TT was 9.9 months. Resection of BM in combination with TT (n = 24) resulted in a superior OS of 31.8 months (95% CI: 16.0-47.6) compared with TT only (n = 40) with an OS of 7.6 months (95% CI: 5.8-9.3). Resection of BM in combination with TT significantly improves the survival of patients with RCC with BM over TT only. Sarcomatoid features and G3/G4 Fuhrman grade are independent factors of poor prognosis.